A computational and experimental study for the optimum reinforcement layout design of an RC frame. Issue 2 (18th April 2016) - Özkal, Fatih Mehmet; Uysal, Habib
Abstract : Purpose: – Compared with conventional design methods, strut-and-tie modeling is a more suitable and even a superior method for the reinforcement layout design of structural members with uncommon geometrical shapes and/or regions essentially subject to shear effects. Because determination of the optimum strut-and-tie model for each of the members is an important task, implementation of a topology optimization method could be useful before the detailing stage. The paper aims to discuss these issues. Design/methodology/approach: – Optimum reinforcement layout of a concrete frame was designed by an integrated approach, which consists of topology optimization and strut-and-tie modeling methods. Subsequently, an experimental comparison of the new model with the conventional model was performed based on their structural behaviors. Findings: – Depending on the experimental results, it was concluded that the new integrated design method presents more successful results than does the conventional method for the design of reinforced concrete members. Originality/value: – The preference of the new method will facilitate the design process by eliminating the experience required of design engineers.